Analysis of Managerial Competencies of School Principals In Improving the Performance of the State Civil Apparatus - Pabida, Luther; Amiruddin, Amiruddin; Dahlan, Dahlan (Universitas Negeri Makassar, 2024)
The disorderly data of users or users of two-wheeled official vehicle assets retired state civil servants is one of the disclaimer opinions on the financial statements of the Biak Numfor local government. This study aims to analyze policy implementation and inhibiting factors in regulating the assets of two-wheeled official vehicles, retired state civil servants at the Regional Finance and Asset Management Agency of Biak Numfor Regency. The method used in this study is qualitative with data analysis techniques through three stages, namely data reduction, data presentation and conclusions. The results of the study found that the implementation of the policy of regulating the assets of the retired state civil apparatus wheel vehicles at the Regional Finance and Asset Management Agency of Biak Numfor Regency, judging from indicators of communication, resources, attitudes or dispositions and bureaucratic structure showed that its implementation was not optimal. This is due to the existence of retired state civil servants who use and control two-wheeled official vehicles and do not return them to the Regional Equipment Organization. There are inhibiting factors in the process of regulating the assets of two-wheeled official vehicles retired state civil servants at the Regional Finance and Asset Management Agency of Biak Numfor Regency, namely miscommunication, incompetent human resources, low capabilities, and bureaucracy that is not conducive. Increasing socialization related to the policy of regulating two-wheeled official vehicle assets of retired state civil servants is an important concern at the Regional Finance and Asset Management Agency of Biak Numfor Regency to optimize the management of two-wheeled service vehicle assets of retired state civil servants.